PENGEMBANGAN BUKU AJAR BAHASA INDONESIA KELAS VI DENGAN PENDEKATAN SKEMATA - Endah Nur Kholifah (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2016)
By the developing of textbook of Bahasa Indonesia using schemata approach for the sixthe graders, hopefully it could be a main guide for students in learning, and the teacher in doing the learning activities in the class, the expected final competence and centered to the students. The process of developing the textbook of Bahasa Indonesia for the sixth graders using schemata was the reasearch and development. The research was aimed to gain the description of the development of textbook for the sixth graders in the first semester using schemata approach. This appeared from the validation result of textbook of Bahasa Indonesia using schemata approach about appropriateness of content, presentation feasibility, and feasibility of languages, are eligible to use. While the result of implementation to the students and the teacher, textbook of bahasa Indonesia using schemata approach also showed the maximum result. By the developing of textbook and implementation of learning model which use schemata approach, pay attention to the selection of meaningful teaching materials, considering the criteria of a good preparation of textbook in accordance with the instructional objectives and expected learning outcomes (final competencies).